Job satisfaction as a predictor of Burnout and Sleep Quality in subway ticket office female employees / Satisfacción laboral como predictor de Burnout y Calidad de Sueño en Taquilleras - Unda Rojas, Sara; Ramírez Pérez, Jazmín (Red de Investigación en Salud en el Trabajo; Vol. 7 Núm. 13 (2024): (Julio-Diciembre), 2024)
Introduction : Ticket office female employees in the subway in Mexico City perform a fundamental job for the efficiency of the subway public transport. However, it is a complicated activity because as part of their work, they are exposed to work stressors, such as violence by the user, low salary, and shifts that can affect their quality of sleep, among others. Therefore, the study's objective was to analyze Job Satisfaction as a predictor of Burnout Syndrome and Sleep Quality in this population of workers. Method: Participants one hundred ticket office female employees, observational, analytical, cross-sectional study with a non-probabilistic sample. Instruments: Job Satisfaction Scale S10/12; Gil-Monte's CESQT and the Mexican Sleep Scale. Results: Job satisfaction is a predictor of Enthusiasm for work, and dissatisfaction with the supervisor is a predictor of Burnout, Psychological Exhaustion, and Indolence at work. Dissatisfaction with benefits at work is a predictor of the Guilt dimension. Dissatisfaction with the supervisor and Psychological Exhaustion are predictors of Sleep Quality. Conclusions: It is recommended for these workers to take breaks, improve their sleep hygiene, and conduct preventive measures.